Evaluating primary endpoints for COVID-19 therapeutic trials to assess recovery - Douin, David J. (2023)
Rationale: Uncertainty regarding the natural history of coronavirus disease (COVID-19) led to difficulty in efficacy endpoint selection for therapeutic trials. Capturing outcomes that occur after hospital discharge may improve assessment of clinical recovery among hospitalized patients with COVID-19. Objectives: Evaluate 90-day clinical course of patients hospitalized with COVID-19, comparing three distinct definitions of recovery. Methods: We used pooled data from three clinical trials of neutralizing monoclonal antibodies to compare: 1) the hospital discharge approach; 2) the TICO (Therapeutics for Inpatients with COVID-19) trials sustained recovery approach; and 3) a comprehensive approach. At the time of enrollment, all patients were hospitalized in a non-ICU setting without organ failure or major extrapulmonary manifestations of COVID-19. We defined discordance as a difference between time to recovery. Measurements and Main Results: Discordance between the hospital discharge and comprehensive approaches occurred in 170 (20%) of 850 enrolled participants, including 126 hospital readmissions and 24 deaths after initial hospital discharge. Discordant participants were older (median age, 68 vs. 59 years; P < 0.001) and more had a comorbidity (84% vs. 70%; P < 0.001). Of 170 discordant participants, 106 (62%) had postdischarge events captured by the TICO approach. Conclusions: Among patients hospitalized with COVID-19, 20% had clinically significant postdischarge events within 90 days after randomization in patients who would be considered "recovered" using the hospital discharge approach. Using the TICO approach balances length of follow-up with practical limitations. However, clinical trials of COVID-19 therapeutics should use follow-up times up to 90 days to assess clinical recovery more accurately.